Analysis of physical exercises to improve physical abilities and shooting in young basketball players - Mohammed J. Monadi; Zaid M. Jabbar; Hussein M. Tuama (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.